The cinema of the Dardenne brothers : responsible realism - Mosley, Philip, 1947- (Wallflower Press Book, 2013)
"The brothers Jean-Pierre and Luc Dardenne have established an international reputation for their emotionally powerful realist cinema. Inspired by their home turf of Liege-Seraing, a former industrial hub of French-speaking southern Belgium, they have crafted a series of fiction films that blends acute observation of life on the social margins with moral fables for the postmodern age. This volume analyses the brothers' career from their leftist video documentaries of the 1970s and 1980s through their debut as directors of fiction films in the late 1980s and early 1990s to their six major achievements from 'The Promise' (1996) to 'The Kid with a Bike' (2011), an oeuvre that includes two Golden Palms at the Cannes film festival, for 'Rosetta' (1999) and 'The Child' (2005). It argues that the ethical dimension of the Dardennes' work complements rather than precludes their sustained expression of a fundamental political sensibility."--Zadní s. obálky
Keywords: Dardenne, Jean-Pierre, -- 1951-; Dardenne, Luc, -- 1954-; filmoví režiséři -- Belgie; filmoví scenáristé -- Belgie; film -- Belgie; film directors -- Belgium; screenwriters -- Belgium; film -- Belgium; studie; studies